ANALISIS KEBUTUHAN AIR BERSIH PADA SISTEM AIR BERSIH MASJID RAUDHATUL ILMI SEKOLAH TINGGI PENERBANGAN INDONESIA - Saiffan Surya Wardanu; Amal Fatkhulloh (Langit Biru: Jurnal Ilmiah Aviasi, 2018)
The main purpose of the clean water system in the Raudhatul Ilmi mosque is none other than to fulfill every need for clean water needed by mosque worshipers and mosque administrators in carrying out spiritual activities, cleaning, and MCK. To achieve this goal, the Raudhatul Ilmi Mosque requires various types of supporting equipment that can provide clean water needs that are in accordance with the needs of the mosque users. The modeling analysis obtained clean water requirements of 11450 liters supported by an additional supply pump with a 7m3 / h debit with a head of 17.86m, and to supply water to the male ablution area a water flow rate of 155.2 l / m was needed.